Citizen Journalism Debacle: A Case Study of Codeblu’s Clairmont Reportage - Ari S. Widodo; Diana Anggraini; Chawla Fatmaduri (Ikatan Sarjana Komunikasi Indonesia, 2026)
The emergence of digital platform has transformed content creators into citizen journalists, often operating outside the ethical principles of professional journalism. This study highlights the conflict between food vlogger Codeblu and Clairmont Patisserie as an illustration of the clash of information production standards between new media and professional journalism. The main objective of this study is to understand in depth how the tension between citizen journalism practices and professional journalism standards affects the public information ecosystem, particularly in verification, accountability and transparency. Using Grounded Theory approach with a constructivist basis from Kathy Charmaz and situational mapping from Adele Clarke. Data was obtained from three main sources: Codeblu viral videos, online media reports (Kompas.com and Liputan6.com) and Clairmont's official statements. The analysis was carried out through qualitative coding, and discursive analysis of the power relations and ethical standards involved. Most studies on citizen journalism in Indonesia have mainly addressed its role in democratizing information and its legal or regulatory implications. However, little is known about the epistemic tension that arises when citizen journalism adopts the form of professional reportage, particularly in viral conflicts such as the Codeblu–Clairmont case. This study fills that gap by critically examining how ethical standards, verification practices, and accountability is negotiated in the digital public sphere.